CREATION OF IN VITRO COLLECTION AND SEEDS CRYOGENIC BANK OF BERBERIS HETEROPODA (Experimental biology, 2022)
The influence of various seed treatment on germination of eight forms of Berberis heteropoda Schrenk was studied. Laboratory germination (LG) of freshly harvested seeds of this species does not exceed 5%. To stimulate seed germination, the following types of treatment were used – exposure to liquid nitrogen (LN) at -196°C for 20 h, stratification in wet perlite for 2 months at 4°C and stratification with preliminary immersion in LN for 20 h. After LN treatment LG increased by an average of 2.8 times. No germination was observed in samples 1-5 and 8 either before or after exposure to LN, presumably due to the high-water content in larger seeds of these forms. It should be noted that stratification accelerates the energy of seed germination, in addition, the LG after stratification averaged 21.6%, which is 5 times higher than the LG of seeds without additional treatments.The obtained shoots were introduced into in vitro culture on Murashige and Skoog medium with 30 g/l sucrose, 0.8 mg/l 6-benzylaminopurine, 0.02 mg/l indolylbutyric acid, 0.1 mg/l gibberellic acid, 1 mg/l ascorbic acid, 1 mg/l calcium pantothenate, 4 g/l agar, 1.75 g/l Gelrite, pH 5.7. The viability of shoots after testing on specialized medium 523 was 46.4%. Seeds of eight accessions of B. heteropoda were placed in a cryogenic bank at -196°C, 3 accessions were placed for long-term storage at -20°C.
Keywords: Berberis heteropoda; seeds; liquid nitrogen; stratification; laboratory germination; in vitro culture; cryogenic bank.